Prospects and challenges of energy storage materials: A comprehensive review - Md Mir Shakib Ahmed; Md. Jahid Hasan; Md. Shakil Chowdhury; Md Khaledur Rahman; Md Saiful Islam; Md Shakhawat Hossain; Md. Aminul Islam; Nayem Hossain; Md Hosne Mobarak (Chemical Engineering Journal Advances)
Energy storage technologies, which are based on natural principles and developed via rigorous academic study, are essential for sustainable energy solutions. Mechanical systems such as flywheel, pumped hydro, and compressed air storage rely on inertia and gravitational potential to store and release energy. On the other hand, electrochemical systems, which include different types of batteries, effectively store and release energy by utilizing materials like metal hydrides and transition metal oxides. These materials are known for their high energy densities and reversible chemical properties. Although they have shown potential, issues such as high costs, limited availability of materials, and negative environmental effects continue to remain. This requires the development of sustainable and scalable production methods and presents difficulties in integrating with current infrastructure. To tackle these problems, a multidisciplinary strategy is necessary. This approach should involve the creation of effective materials, the implementation of sustainable manufacturing methods, and the establishment of comprehensive policy frameworks. Enhanced global collaboration and increased investment in research and development are crucial as well. Through promoting collaboration among scientists, engineers, policymakers, and industry stakeholders, we can address existing constraints, improve energy efficiency, and advance the ability of the energy sector to withstand challenges. This will enable the development of a strong, environmentally friendly energy future that can meet global energy needs in a sustainable and fair manner.